Tindak Pidana Pencurian Data Dan Privasi Pengguna Dalam Transaksi E-Commerce : Studi Kasus Pada Aplikasi Tokopedia - Akila Nuranisa; Diana Lukitasari (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The development of information and communication technology facilitates transactions, including through e-commerce, but has the potential to present criminal acts of data theft and violations of user privacy. This research investigates the case of data leakage in the Tokopedia application in criminal law and corporate liability by Tokopedia. The analysis shows that Tokopedia can be criminally liable for its negligence in maintaining the security of personal data, such as the weakness of the data security system (encryption) and the lack of vigilance against hacker attacks. Tokopedia has several obligations in protecting users' personal data. This case shows the importance of corporate criminal liability and the company's obligation to protect users' personal data. Using the normative juridical method and statutory approach, primary data is obtained from the Tokopedia 2020 case study, while secondary data comes from primary and secondary legal sources. The results show that the Tokopedia data leak in 2020 is a criminal offense due to the negligence of PT Tokopedia, which is in accordance with the criminal law principle of Culpa Lata Unconscious. The Personal Data Protection Law emphasizes the responsibility of PT. Tokopedia in protecting personal data. Law enforcement needs to take firm action against the perpetrators of criminal acts to provide a deterrent effect.